Java Development with Ant - Hatcher, Erik (Manning Publications, 2011)
Encompassing Java-centric software project best practices for designing and automating build, test, and deployment processes using ANT, this book is written for developers using Java in large software projects and those who have reached the limits of classic IDE development systems. Benefiting developers who apply extreme programming methodology to Java projects, this resource provides detailed coverage of ANT and explains how to use it in large projects and extend it when needed. In addition to using ANT for Java applications, it includes discussions of servlets and J2EE applications, which cover the majority of Java development projects.